Effect of the Ammonium Nitrate Levels on Intercropped Barley (Hordeum Vulgare L.) and Vetch (Vicia Villosa) under Weed Competition Manag - F Faramarzi; S. M. B Hosseini; H Mansouri; D Fangueiro; H Alizadeh (پژوهشهای زراعی ایران, 2022)
IntroductionIntensive agriculture, despite high production, has adverse environmental effects, mainly due to the use of pesticides and chemical fertilizers. Therefore, we need alternative agricultural systems that are more economically and environmentally sustainable to produce crops. One of the sustainable methods in the production of agricultural products is intercropping. Intercropping of two or more species in a plot of land can increase biodiversity and resource utilization as agricultural perspective, which in turn can lead to increased yield stability. Intercropping uses resources more efficiently than monoculture, preventing the growth and spread of weeds by shading and suffocating weeds, and in some cases with allelopathic. Intercropping of cereals and legumes is recommended for the development of sustainable food production systems, especially in planting systems based on reduced consumption of foreign inputs. The importance of these systems depends on the nitrogen stabilized by the legumes. The aim of this experiment was to study the effects of row intercropping of barley and vetch and different levels of ammonium nitrate fertilizer on weed biomass, yield components and yield of two species in Karaj climatic condition.Materials and MethodsThis experiment was performed as a factorial split plot based on randomized complete block design in 2019-2020 cropping year in the research farm of the Agriculture and Natural Resources, University of Tehran. Main plots included three levels of ammonium nitrate fertilizer (0, 35 and 70 kg.ha-1) and sub-plots include different ratios of barley and vetch (100% barley, 80% barley: 20% vetch, 80% barley: 45% vetch, 80% barley: 70% vetch, 100% vetch, 80% vetch: 20% barley, 80% vetch: 45% barley, 80% vetch: 70% barley) weeding and non-weeding were in three replications. Plant density in sole barley and vetch were 250 plants per square meter. The method of cultivation in this study was additive intercropping. Seeds were sown on November 6th. The first stage of fertilization was done simultaneously with planting and one third was added to each plot and the second and third stages of fertilization were performed in two stages of stem emergence and spike emergence, respectively from ammonium nitrate fertilizer source. The final harvest was done on July 28th. Data were analyzed using SAS 9.1 software. The least significant difference test (P≤0.05) was used to compare the means.Results and DiscussionThe highest barley grain yield (432.44 g) was related to sole barley, 70 kg ammonium nitrate and weed control, which was not significantly different with 80% B: 45%V, 70 kg ammonium nitrate and weed control. Also, the highest yield of vetch grain (161.47 g) was obtained in sole vetch, application of 70 kg ammonium nitrate and weed control treatment, which was not significantly different with 80%V: 20%B intercropping, application of 70 kg ammonium nitrate and weed control treatment. Weeds in this experiment include: Wild oats (Avena fatua), ryegrass (Lolium temulentum), Bromus (Bromus tectorum), Fox tail (Alopecurus myosuroides), Wild mustard (Sinapis arvensis), Creeping Thistle (Cirsium arvense), London rocket (Sisymbrium irio), Cockspur grass (Echinochloa crus-galli) and Cornflower (Centaurea cyanus). The highest dry weight of weed (231.62 g) was observed in sole vetch, application of 70 kg.ha-1 ammonium nitrate fertilizer treatment. The highest land equivalent ratio LER (1.68) is related to 80% V: 70%B, non-application of ammonium nitrate fertilizer in weed control condition. Intercropping was successful in controlling weeds and using resources, thereby increasing the yield of plants in the experiment.ConclusionThe results obtained from the experiment showed that all different systems of barley and vetch intercropping had land equivalent ratio higher than one, which indicates the superiority of intercropping over pure crops in the land use and crop production. Intercropping treatments were also able to control weeds. Intercropping with high ability to suppress weeds were able to use more resources. On the other hand, vetch biologically stabilized nitrogen was able to reduce the need for fertilizer in plants.